O budownictwie nie tylko przemysłowym - Kajzer, Leszek (Zeszyty Wiejskie, 2014)
A significant part of youthful professional activity of the learned Addressee of this volume, Mr Władysław Baranowski, called Sławek by friends, was connected with working on and writing subsequent journals of series entitled “Catalogue of Landmarked Buildings of Industrial Construction in Poland”. The initiative of registering theses objects and publishing their catalogues emerged in the mid 1950s of the 20th century among scientists who deal with the broadly defined history of material culture as well as the history and ethnography which then as a result of disappearance of a traditional image of the Polish countryside started its movement towards ethnology. A few years earlier the Institute of the History of Material Culture of the Polish Academy of Sciences was established in Warsaw and it was a scientific unit of basic importance for archeologists and ethnographers as well as historians who love historic processes and objects more than dates, battles, dead bodies and blood that is shed from traditional history schoolbooks.